2018
DOI: 10.1111/bju.14528
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of metabolic syndrome and lifestyle on the prevalence of benign prostatic hyperplasia requiring treatment: historical cohort study of 130 454 men

Abstract: MetS and its components, particularly low HDL-C levels, were strongly correlated with an increased prevalence of BPH requiring treatment. In addition, moderate alcohol intake and elderly men from lower socioeconomic strata were associated with a decreased prevalence of BPH requiring treatment in our cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…Recently, several studies have reported that metabolic syndrome (MetS) is associated with an increased prevalence of BPH 8,9 . Our study group also reported similar results using the National Health Information Database of the National Health Insurance Service in South Korea 10 . Moreover, our study group also reported that, among the components of MetS, a decreased high‐density lipoprotein (HDL) cholesterol level was the most powerful variable associated with an increased prevalence of BPH, 10 which was consistent with the findings of previous studies 11,12 .…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…Recently, several studies have reported that metabolic syndrome (MetS) is associated with an increased prevalence of BPH 8,9 . Our study group also reported similar results using the National Health Information Database of the National Health Insurance Service in South Korea 10 . Moreover, our study group also reported that, among the components of MetS, a decreased high‐density lipoprotein (HDL) cholesterol level was the most powerful variable associated with an increased prevalence of BPH, 10 which was consistent with the findings of previous studies 11,12 .…”
Section: Introductionsupporting
confidence: 86%
“…A total of 130 342 men who had a national health checkup in 2009 were initially selected. We excluded those without information on MetS, as previously described 10 . Among these men, 36 854 men with BPH in 2009 were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations